Infrastructure, urbanization, and demand for bank and non-bank loans of households in the People's Republic of China - Angela C. Lyons; John E. Grable; Ting Zeng (Asian Development Bank Institute (ADBI), 2017)
Financial inclusion plays an important role in giving households greater access to borrowing opportunities, which in turn can be used to improve human capital accumulation, socioeconomic status, and long-run economic development. One way to enhance households' access to and usage of the financial system, especially the formal banking system, is to ensure that an adequate infrastructure exists within their community. This study uses data from the 2013 Chinese Household Finance Survey to investigate how the infrastructure affects the usage of formal bank loans for both urban and rural households in the People's Republic of China (PRC). The analysis is extended to investigate the impacts of the infrastructure on non-bank loans. The results suggest that the infrastructure, in a variety of forms (e.g., physical, financial, technological, social, and informational), is significantly associated with the loan demand - most notably for urban households using formal bank loans. Further, those living in more urbanized areas and megacities are less likely to demand bank and non-bank loans even after controlling for other factors, suggesting that there may be an "urbanization effect" that is dampening credit access and usage. The potential endogeneity between the infrastructure and the loan demand is taken into consideration. The results show that decisions related to the loan demand and infrastructure mostly appear to be made independently. The findings from this research have important implications for the PRC and other countries working on national strategies aimed at improving financial inclusion, especially the expansion of bank credit in rapidly growing urbanized areas, where the infrastructure may be reaching capacity.
Keywords: D1; G2; O1; I3; J1; 330; infrastructure; urbanization; financial inclusion; microfinance; credit; PRC